(untitled) (MAUSAM, 1962)
Begumpet (Lat. 17°27’ N, Long. 78°28’E) is an important aerodrome in the aviation map of India. Main aviation hazards here during the pre-monsoon and monsoon periods include thunderstorm activity with associated surface squalls. A study of the features of the surface squalls during the year is made in this paper, with the aid of the anemo-grams and barograms of Begumpet. This study is made more or less on the lines of Ra,makrislman(1957).